The IMAGINE instrument: first neutron protein structure and new capabilities for neutron macromolecular crystallography. (8th October 2013) - Meilleur, Flora; Munshi, Parthapratim; Robertson, Lee; Stoica, Alexandru D.; Crow, Lowell; Kovalevsky, Andrey; Koritsanszky, Tibor; Chakoumakos, Bryan C.; Blessing, Robert; Myles, Dean A. A.
<x xml:space="preserve">Abstract</x> The first high‐resolution neutron protein structure of perdeuterated rubredoxin from Pyrococcus furiosus (PfRd) determined using the new IMAGINE macromolecular neutron crystallography instrument at the Oak Ridge National Laboratory is reported. Neutron diffraction data extending to 1.65 Å resolution were collected from a relatively small 0.7 mm3PfRd crystal using 2.5 d (60 h) of beam time. The refined structure contains 371 out of 391, or 95%, of the D atoms of the protein and 58 solvent molecules. The IMAGINE instrument is designed to provide neutron data at or near atomic resolution (1.5 Å) from crystals with volume <1.0 mm3 and with unit‐cell edges <100 Å. Beamline features include novel elliptical focusing mirrors that deliver neutrons into a 2.0 × 3.2 mm focal spot at the sample position with full‐width vertical and horizontal divergences of 0.5 and 0.6°, respectively. Variable short‐ and long‐wavelength cutoff optics provide automated exchange between multiple‐wavelength configurations (λmin = 2.0, 2.8, 3.3 Å to λmax = 3.0, 4.0, 4.5, ∼20 Å). These optics produce a more than 20‐fold increase in the flux density at the sample and should help to enable more routine collection of high‐resolution data from submillimetre‐cubed crystals. Notably, the crystal used to collect these PfRd data was 5–10 times smaller than those previously reported.